2014
DOI: 10.1021/jp504369z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Surface and Subsurface Oxygen Reactivity and Dynamics with CO Adsorbed on Rh(111)

Abstract: The translational and angular intensity dependence of CO 2 produced from the reaction of CO with an initial oxygen coverage of 0.5 ML ≤ Θ O ≤ 1.6 ML on Rh(111) at a surface temperature of 450 K was measured. This range of coverages goes from only surface absorbed O to both adsorbed and selvedge absorbed O. The measured CO 2 translational energy is independent of Θ O and is larger than steady-state experiments [Colonell et al. J. Chem. Phys. 1995, 103, 6677], which were done at lower O coverages, but follows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Despite the advances in gPK modeling, kinetic Monte Carlo (KMC) simulations are now often the method of choice that is used to determine and verify the surface dynamics and steady state values in surface catalysis problems [25][26][27][28][29][30][31][32][33][34][35] . KMC algorithms are stochastic realizations of the surface dynamics that probabilistically update the state of some surface with large but finite size.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in gPK modeling, kinetic Monte Carlo (KMC) simulations are now often the method of choice that is used to determine and verify the surface dynamics and steady state values in surface catalysis problems [25][26][27][28][29][30][31][32][33][34][35] . KMC algorithms are stochastic realizations of the surface dynamics that probabilistically update the state of some surface with large but finite size.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the emergence of O sub from highly oxidized surfaces including the RhO 2 surface oxide and the surface reconstructions of the (2 × 1)-O, (2 × 2)-3O, and (2 √ 3 × 2 √ 3)­R30° as well as desorption of surface oxygen from oxygen-induced surface reconstructions will provide insight into the reactivity of the metal under industrial catalytic conditions. O sub are mobile O atoms dissolved in the selvedge of the metal and not strongly bound to Rh atoms as are O in the oxides. , Because O sub resides in the near surface region of the metal, it can be challenging to study as its presence is often screened by surface atoms. ,,,, Previous studies have determined that O sub participates in surface reactions, enhances the rate of reaction by acting as an oxygen source, and replenishes the active oxygenaceous surface phase. , Furthermore, O sub formation affects the resultant surface structures by promoting the growth of oxides on the surface. ,, As defect sites and step edges on single crystal surfaces promote initial adsorption and subsequent reaction, , it follows that O sub emergence could occur along step edges and defect sites, although no direct evidence of this has been observed. A recent study showed that the presence of defects alone was insufficient to form O sub .…”
mentioning
confidence: 99%
“…For example, a trilayer surface oxide forms on Rh under conditions similar to those for Ir and Pd, and the oxide trilayer has been hypothesized to form on Ru, although this has yet to be experimentally observed. Additionally, O 2 readily dissociates on these surfaces, forming adlayers of known structure and composition . While O 2 dissociates into O ad on Rh(111) and saturates at an oxygen coverage (θ O ) of 0.5 monolayers (ML, 1.6 × 10 15 O cm –2 ) in a (2 × 1)-O adlayer, the rate of O sub formation from O ad is slow . Furthermore, high pressures of molecular oxygen are necessary to form high oxygen phases and O sub . , In order to generate higher amounts of O sub , gas-phase atomic oxygen (AO) is used because it is much more likely to be absorbed.…”
mentioning
confidence: 99%
See 2 more Smart Citations